The Positive Emotion of Love: Through the Lens of Islamic Teachings - Fariha Qadir Mela (jihat-ul-islam, 2021)
Positive emotions are defined as brief experiences, which feel good in the present and increase the chances that one will feel good in the future also. They probably are the most fundamental constituents in the formula of living a content life. Barbara Fredrickson has pointed out ten positive emotions out of many, which she feels are important for personal and societal wellbeing. Out of these ten she deems love to be the strongest, which takes in all other positive emotions. This article delves into the depth of “love” through the lens of Qur’an and Sunnah, analyzing how Islam brings to life this beautiful emotion and channelizes it in the direction, which guarantees ultimate wellbeing of people, societies and nations